2015
DOI: 10.17795/semj27942
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Plus Dry Needling, an Effective Treatment Method for Chronic Neck Pain

Abstract: Background:In recent years, acupuncture has attracted much attention as a complementary therapy in the management of chronic neck pain, but the definite effect of this method has not yet been proven in reducing pain and improving function. Objectives: This study was conducted to evaluate the effects of acupuncture plus dry needling in relieving chronic neck pain and its lasting effects for up to 3 months after treatment. Patients and Methods: Thirty-eight patients with chronic neck pain were included in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Considering the effect size of 0.4 in the previous study (25), the sample size was calculated based on an assumed study power of 80% (β = 0.2) and a false-positive rate of 5% (α = 0.05). Using these parameters, and adjusting α for multiple comparisons, as well as including the possible loss of 25% of the samples through the study, we required at least 30 patients in each group.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the effect size of 0.4 in the previous study (25), the sample size was calculated based on an assumed study power of 80% (β = 0.2) and a false-positive rate of 5% (α = 0.05). Using these parameters, and adjusting α for multiple comparisons, as well as including the possible loss of 25% of the samples through the study, we required at least 30 patients in each group.…”
Section: Sample Sizementioning
confidence: 99%
“…Reviewing the studies in this regard shows that not only the evidence of the effect of acupuncture is limited but also some studies have demonstrated that acupuncture was not significantly different from sham needle insertion. It is emphasized in the literature that further well-designed studies are required in the subject (17)(18)(19)(20)(21)(22)(23)(24)(25). Several studies have evaluated the effects of acupuncture or exercise on non-specific CNP, while the evidence for the efficacy of exercise on radicular neck pain is inconclusive (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%